2019
DOI: 10.14309/ctg.0000000000000088
|View full text |Cite
|
Sign up to set email alerts
|

Novel Circulating Tumor Cell Assay for Detection of Colorectal Adenomas and Cancer

Abstract: OBJECTIVES:There is a significant unmet need for a blood test with adequate sensitivity to detect colorectal cancer (CRC) and adenomas. We describe a novel circulating tumor cell (CTC) platform to capture colorectal epithelial cells associated with CRC and adenomas.METHODS:Blood was collected from 667 Taiwanese adults from 2012 to 2018 before a colonoscopy. The study population included healthy control subjects, patients with adenomas, and those with stage I–IV CRC. CTCs were isolated from the blood using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 29 publications
(38 reference statements)
0
28
0
2
Order By: Relevance
“…Considering the low occurrence of CTCs in the bloodstream during CRC metastatic process, the utilization of CTCs for a screening of CRC early stages or precancerous lesions represents a very ambitious aim. The recent study of Tsai et al [134] has accepted this challenging topic. On the day of the colonoscopy, 8 ml of peripheral blood was collected from 667 Taiwanese subjects (in detail the study consisted of 235 healthy controls, 107 subjects with adenomatous polyps, and 325 patients with CRC across all stages I-IV).…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%
“…Considering the low occurrence of CTCs in the bloodstream during CRC metastatic process, the utilization of CTCs for a screening of CRC early stages or precancerous lesions represents a very ambitious aim. The recent study of Tsai et al [134] has accepted this challenging topic. On the day of the colonoscopy, 8 ml of peripheral blood was collected from 667 Taiwanese subjects (in detail the study consisted of 235 healthy controls, 107 subjects with adenomatous polyps, and 325 patients with CRC across all stages I-IV).…”
Section: Circulating Tumor Cells (Ctcs)mentioning
confidence: 99%
“…However, we cannot ignore the potential harm causing by advanced adenomas, and the existing data are not complete enough for patients to stop all further treatment after the adenoma is removed. 16 Our findings showed that disorders of glucose and lipid metabolism affect the progression of advanced adenomas, so the analysis of colorectal adenomas becomes extremely important.…”
Section: Discussionmentioning
confidence: 78%
“…The isolation and capture of CTCs based on biological characteristics of those heterogeneous cells utilize different biological markers expressed in the cells ( Table 2 ) [ 18 , 19 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 45 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. The first data describing the detection and characterization of carcinoma cells in the systemic circulation (bone marrow) based on cytokeratin and MUC-1 glycoprotein expression in epithelial cancer cells, but not in healthy cells, were published 25 years ago [ 63 ].…”
Section: Ctc Isolation and Detection Techniquesmentioning
confidence: 99%